Endovascular Treatment of Acute Stroke Due to Intracranial Atherosclerotic Stenosis–Related Large Vessel Occlusion - Park, Hyungjong; Baek, Jang-Hyun; Kim, Byung Moon (Frontiers in Neurology, 2019)
Modern endovascular treatment (EVT) has become a standard treatment for acute ischemic stroke due to large vessel occlusion (LVO) in the anterior circulation. However, whether modern EVT tools used for intracranial atherosclerotic stenosis (ICAS)-related LVO are as safe and effective as for use in embolic LVO remains unclear. There have been only a few studies about EVT for ICAS-related LVO, and these studies revealed that modern thrombectomy with a stent retriever or contact aspiration was less effective and more time consuming in ICAS-related LVO than in embolic LVO. Because fast and successful recanalization (defined as modified Thrombolysis in Cerebral Ischemia grade, 2b or 3) is the most critical factor influencing favorable outcomes, it is important to determine the appropriate EVT strategy for fast recanalization of ICAS-related LVO. In this report, we review the results of modern thrombectomy using stent retriever or contact aspiration and rescue treatments after failure of modern thrombectomy for ICAS-related LVO. Finally, we propose the EVT strategy appropriate for ICAS-related LVO based on a literature review and our experience.